Definiteness, Uniqueness, and Maximality in Languages With and Without Articles. (30th May 2020) - Šimík, Radek; Demian, Christoph
Abstract: We present a number of experiments testing influential hypotheses about the meaning of definite descriptions (in languages with articles, represented here by German) and bare nominals (in articleless languages, represented here by Russian). Our results are in line with the commonly entertained hypothesis that definite descriptions convey uniqueness (if singular) or maximality (if plural), but fail to support two hypotheses about bare nominal interpretation, namely that singular bare nominals convey uniqueness ( Dayal 2004 ) and that topical bare nominals convey uniqueness/maximality ( Geist 2010, among many others). Uniqueness or maximality inferences are expected to arise via covert type-shifting under these approaches. Our results are compatible with what we take to be the null hypothesis, namely that bare nominals in articleless languages are existential and free of presuppositional semantics, even if they correspond—in their use—to definite descriptions ( Heim 2011 ).